Compensation of acetabular defects in primary and revision hip arthroplasty - Maria Yu. Udintseva; Elena A. Volokitina; Denis A. Kolotigin; Sergey M. Kutepov (Гений oртопедии)
Introduction Total hip arthroplasty in defects of the acetabulum is a complex type of surgical intervention, and the search for optimal implants and bone substituting materials to restore the integrity of the acetabulum is one of the current problems. The aim of the work was to analyze the results of primary and revision hip arthroplasty with compensation of acetabulum defects. Materials and methods The study material consisted of 93 patients with primary (65) and revision (28) total hip arthroplasty in the presence of bone defects of the acetabulum of varying severity. To systematize primary defects, the classification of the American Association of Orthopedic Surgeons (AAOS, 2017) was used; for defects in revision surgeries, the classification of W.G. Paprosky (1994) was used. Clinical, radiological, and statistical study methods were used. The results of managing bone defects of the acetabulum with various methods of compensation were studied. The Harris Hip Score (HHS), 1969, was used to assess the function of the involved joints. Results Depending on the type of acetabular defects, an algorithm was developed for choosing a bone grafting method for acetabular defects and implanting the cup. The best results were observed for cases of a combination of resorbable and non-resorbable bone graft materials and cementless fixation of the pelvic component. A clinical example of three consecutive revision interventions on one hip joint in a patient with bilateral dysplastic coxarthrosis is presented. Discussion The most widely used method of bone grafting in primary arthroplasty is plastic surgery with autologous chips from the femoral head. In significant bone tissue loss, one of the plastic surgery options is a structural auto- or allograft, the use of which allows restoring the rotation center and forming a bone support for possible future revisions; poor results with this method are caused by allograft lysis. In revision arthroplasty on the hip joint in large defects, plastic surgery of the defect is performed with crushed or structural allograft bone. An antiprotrusion constructs or cups made of trabecular metal are installed; in instability of the pelvic ring, osteosynthesis of the posterior column is required. Trabecular metal structures feachuring high porosity and adhesion to bone and the elastic modulus close to bone tissue provide conditions for optimal primary and secondary fixation of the component. Conclusion Long-term and painless functioning of the hip joint after arthroplasty performed for acetabular defects is possible with restoration of the spherical shape of the acetabulum and the center of joint rotation in the true acetabulum, adequate elimination of bone tissue loss, reliable primary fixation of the cup with provision of conditions due to restoration and osteointegration. Acetabular defects are diverse in their anatomical manifestations, which create difficulties in choosing pelvic components, augments, and the method of their fixation to the pelvic bone. Based on the type of the acetabular defect, an algorithm has been developed for choosing a method for acetabular bone defect filling and implanting a cup.